Cost-Effectiveness of Single-Inhaler Versus Multiple-Inhaler Triple Therapy in COPD: A German Healthcare Perspective - Beeh KM; Claussen J; Shah D; Martin A; Kendall R; Dasari P; Ismaila AS; Noorduyn SG (International Journal of COPD)
Kai-Michael Beeh,1,* Jing Claussen,2,* Dhvani Shah,3 Alan Martin,4 Robyn Kendall,5 Priyadarsini Dasari,6 Afisi S Ismaila,7,8 Stephen G Noorduyn7,9 1Insaf Respiratory Research Institute, Taunusstein, Germany; 2Global Medical Affairs, GSK, Munich, Germany; 3Insights, Evidence and Value – Health Economics & Epidemiology, ICON Plc, NJ, USA; 4Value Evidence and Outcomes, GSK, Brentford, Middlesex, UK; 5ICON Health Economics, ICON Plc, Vancouver, Canada; 6Insights, Evidence and Value – Health Economics & Epidemiology, ICON Plc, Houston, TX, USA; 7Department of Health Research Methods, Evidence and Impact, McMaster University, Hamilton, Ontario, Canada; 8Value Evidence and Outcomes, GSK, Collegeville, PA, USA; 9Value Evidence and Outcomes, GSK, Ontario, Canada*These authors contributed equally to this workCorrespondence: Jing Claussen, Global Medical Affairs, GSK, Munich, Germany, Tel +4915259965322, Email jing.x.claussen@gsk.comPurpose: The INTREPID trial showed that once-daily single-inhaler triple therapy (SITT) using fluticasone furoate, umeclidinium, and vilanterol (FF/UMEC/VI) offers clinical benefits versus non-ELLIPTA multiple-inhaler triple therapy (MITT) for the management of chronic obstructive pulmonary disease (COPD) in real-world clinical practice. This analysis evaluated the cost-effectiveness of SITT with FF/UMEC/VI versus non-ELLIPTA MITT for treating symptomatic COPD from a German healthcare perspective.Patients and Methods: Data from the INTREPID trial, including baseline characteristics, treatment effects (forced expiratory volume in 1 second and St. George’s Respiratory Questionnaire score [derived from exploratory COPD assessment test score mapping]), and discontinuation rates, along with German healthcare resource and drug costs (2023 Euros), were used to populate the GALAXY COPD model. The analysis was conducted over a lifetime horizon, with outcomes including life years (LYs), quality-adjusted LYs (QALYs), and incremental cost-utility ratios. The robustness of the analysis was assessed using scenario, one-way sensitivity, and probabilistic analyses.Results: Improved lifetime outcomes were predicted for FF/UMEC/VI versus non-ELLIPTA MITT, providing additional LYs of 0.174 (95% range: 0.065, 0.322) and QALYs of 0.261 (0.186, 0.346) per patient, together with cost savings of € 2,850 (€ 3,517, € 2,220). Additionally, patients receiving FF/UMEC/VI were predicted to experience a reduction in exacerbations (− 0.063), highlighting its dominance as the preferred treatment option. These findings remained consistent across one-way sensitivity, scenario, and probabilistic analyses, highlighting the robustness of FF/UMEC/VI as a cost-effective solution for COPD management in Germany.Conclusion: FF/UMEC/VI offers clinical benefits and cost savings compared with non-ELLIPTA MITT, suggesting that it may reduce the burden of COPD in Germany and warranting consideration as a preferred treatment option by physicians.Keywords: chronic obstructive pulmonary disease, cost-effectiveness, Germany, fluticasone furoate/umeclidinium/vilanterol, single-inhaler triple therapy, multiple-inhaler triple therapy